Pemanfaatan Sistem Informasi Geografis (SIG) untuk Pemetaan Wilayah Kelompok Tani: Syahrun Mubarak - Syahrun Mubarak (Sumber Penyuluhan Pertanian Indonesia, 2023)
Farmer's group is an institution that formed by the similarity of work, domicile, social, business commodities, and had an accumulation of land area of the members. The group approach is intended to increase the effectiveness and efficiency of implementing agricultural activities. As a production unit, farmer groups have a land area that cannot be separated in the agricultural sector, therefore it is very important to know the land area of farmer groups. One method to determine and measure the area of a farmer group is the mapping method by Geographic Information Systems (GIS). Utilization of Geographic Information Systems (GIS) is a method that can be used to measure and determine the area of land from the spatial aspect. This activity has been conducted from September 2021 to May 2022 in Bonto Loe Village, Bissappu Subdistrict, Bantaeng Regency, South Sulawesi. The purpose of using the Geographic Information System (GIS) is to map the area of the farmer group from the spatial aspect, to measure the area of land and to determine the boundaries of the area of the farmer group. The benefits of using GIS for mapping farmer group areas are a reference for consideration in government policy making in agriculture sector. Utilization of GIS produces a map of the farmer group area which consists of 17 group areas. The total area of farmer groups obtained is 316.62 ha.